2019
DOI: 10.1016/j.neurobiolaging.2018.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Functional network resilience to pathology in presymptomatic genetic frontotemporal dementia

Abstract: The presymptomatic phase of neurodegenerative diseases are characterized by structural brain changes without significant clinical features. We set out to investigate the contribution of functional network resilience to preserved cognition in presymptomatic genetic frontotemporal dementia. We studied 172 people from families carrying genetic abnormalities in C9orf72, MAPT, or PGRN. Networks were extracted from functional MRI data and assessed using graph theoretical analysis. We found that despite loss of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 48 publications
6
47
0
Order By: Relevance
“…The mechanisms that could give rise to changes in circuit function, such as changes in synaptic strength or plasticity ( Benussi et al, 2016 ), may be more amenable to intervention than later stages after neuronal loss begins. Finding that C9+ carriers remain asymptomatic despite reduced connectivity is consistent with a graph theory analysis that reported that the efficiency of intracortical networks remains resilient to declining functional connectivity and focal atrophy until just prior to the onset of clinically manifest disease in carriers of FTD genes ( Rittman et al, 2019 ). Because the average age of our presymptomatic cohort was a decade younger than that of the symptomatic cohort, longer follow-up will be needed to determine whether the functional connectivity changes observed here are predictive of disease onset or allow identification of C9+ carriers at an earlier stage of disease.…”
Section: Discussionsupporting
confidence: 81%
“…The mechanisms that could give rise to changes in circuit function, such as changes in synaptic strength or plasticity ( Benussi et al, 2016 ), may be more amenable to intervention than later stages after neuronal loss begins. Finding that C9+ carriers remain asymptomatic despite reduced connectivity is consistent with a graph theory analysis that reported that the efficiency of intracortical networks remains resilient to declining functional connectivity and focal atrophy until just prior to the onset of clinically manifest disease in carriers of FTD genes ( Rittman et al, 2019 ). Because the average age of our presymptomatic cohort was a decade younger than that of the symptomatic cohort, longer follow-up will be needed to determine whether the functional connectivity changes observed here are predictive of disease onset or allow identification of C9+ carriers at an earlier stage of disease.…”
Section: Discussionsupporting
confidence: 81%
“…We hypothesize that neuromodulatory deficits in patients can cause a loss of prior precision relative to the sensory input, which subsequently leads to apathy. Furthermore, higher order prior beliefs about desired outcomes may fail to appropriately contextualize lower level representations about sensory input due to structural and functional abnormalities in prefrontal and temporal brain regions ( Rittman et al, 2019 ). Further work is required to establish the synaptic and molecular basis of aberrant precision, aided by the parameterization of the precision of an individual’s prior.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 Research in presymptomatic carriers of a hexanucleotide repeat expansion in the C9orf72 gene (preSxC9) reported the occurrence of cognitive and behavioral changes, neuropsychiatric symptoms, and degeneration of gray matter (GM) and white matter (WM). 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 …”
Section: Introductionmentioning
confidence: 99%